Factors Driving Online Impulsive Buying Behavior in Urban Women (Case Study of Shopee, Tiktok Shop and Tokopedia) - Agi Pratama; Masruri Masruri; Tintus Noviyanto; Peri Akbar Manaf (Return : Study of Management, Economic and Bussines, 2025)
Urban women's huge demands on fashion continue to encourage them to buy goods practically through e-commerce. However, it is not uncommon for the purchase process to tend to be impulsive. This study examines the role of cognitive and affective responses in the relationship between internal and external stimuli to e-commerce-based impulse purchases. This study involved 593 urban women living in Jabodetabek area, purchasing online through e-commerce, and the sample collection process took place from October to December 2024. This data was obtained using an online questionnaire and an analysis method in the form of regression using the Structural Equation Modelling (SEM) technique. The results of the study show that the utilitarian browsing  variable has a direct effect on hedonic browsing. Quality of information, visual appeal, variety of selection, navigability, product availability and trust propensity have a direct effect on online impulsive buying. The hedonic browsing  variable significantly mediated the influence of quality of information and navigability on online impulsive buying. and utilitarian browsing significantly moderated the relationship between trust propensity and self-confidence to online impulsive buying. Therefore, understanding the stimuli that can affect online purchases in e-commerce can help businesses in producing better marketing strategies and being able to personalize consumer needs with certain characteristics.